2005
DOI: 10.1152/ajprenal.00032.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal steroid regulation of renal injury in renal wrap hypertension

Abstract: Renal injury is greater in male compared with female rats after renal wrap (RW) hypertension. We investigated the role of gonadal steroids in the sex differences in RW disease severity in male (M) and female (F), castrated (Cast), and ovariectomized (OVX) rats and after dihydrotestosterone (DHT) and 17beta-estradiol (E2) treatment. Male castration attenuated the severity of RW-induced glomerulosclerosis (GS) [GS index (GSI): RW-M, 2.1 +/- 0.2; RW-Cast, 1.3 +/- 0.2; RW-Cast+DHT, 2.4 +/- 0.4], mean glomerular vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 23 publications
7
44
0
Order By: Relevance
“…Previous studies utilizing the ovariectomy model of menopause have demonstrated the dramatic impact that the loss of estrogen has on the development of hypertension in several rodent models, e.g., ANG II, renal wrap, and high-salt diet (13,24,39). In the present study, we demonstrate that during the transition from perimenopause into menopause the hypertensive response to ANG II infusion is augmented in female mice.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies utilizing the ovariectomy model of menopause have demonstrated the dramatic impact that the loss of estrogen has on the development of hypertension in several rodent models, e.g., ANG II, renal wrap, and high-salt diet (13,24,39). In the present study, we demonstrate that during the transition from perimenopause into menopause the hypertensive response to ANG II infusion is augmented in female mice.…”
Section: Discussionsupporting
confidence: 67%
“…This group has not determined whether there are sex differences in oxidative stress in their model, however. In contrast, Ji and colleagues (30) reported that, in rats with "renal wrap hypertension" and high-salt diet, there was no difference in blood pressure between males and females. Despite the lack of a difference in blood pressure in this latter study, the males exhibited higher levels of oxidative stress, as determined by measuring urinary malondialdehyde, renal cortical NADPH oxidase activity, and expression of NADPH oxidase subunit p22 phox .…”
Section: Oxidative Stress In Other Animal Models Of Hypertensionmentioning
confidence: 89%
“…Sexual dimorphism in response to renal disease has been noted for many years. There are gender differences in many renal disease models, including age-related glomerular injury (Baylis 1994), hypertension (Ji et al 2005), polycystic kidney disease (Stringer et al 2005) and diabetic nephropathy (Tomiyoshi et al 2002). In recent years experimental science is now producing tantalizing clues that gender differences also play a role in the kidney's response to ischemia.…”
mentioning
confidence: 99%